Malaysia towards an ageing country - Nik Norliati Fitri Md Nor; Suriati Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2021)
An increase in the number of the elderly population (aged 60 and above) is a global phenomenon, specifically in the developed and developing countries. This is due to development in terms of socioeconomic status such as improved education, healthcare, employment, increasing life expectancy, as well as decreasing fertility and mortality rate of these countries. In fact, Malaysia also has had an increase in population growth and will become an ageing country by 2030. Statistics show that there is an increase in the number of elders aged 60 and above, while the percentage of the young people aged 14 and below decreases over the years. The growing number of elders results in socioeconomic and political issues in these countries due to healthcare costs, as well as economic, physical, and social support from family members, community and policymakers in terms of living arrangements. This article will discuss about some policies and planning with regards to the elders, but the author shall focus on policies and planning related elderly support from their family, especially from the children. This article secondary sources such as previous studies, statistical data on the improvement of the elders, newspapers and official websites. It is aimed to help the Malaysian government in reviewing the current policies and further focus on strategies and plans that require the children to support their elders and prevent the issue of elderly neglect as being highlighted in the news.